Movimentação de Nutrientes em Latossolo Argiloso sob Sistema Plantio Direto - Borgmann, Claudia (2019)
The crops grain yeld is conditioned by the genetic characteristics of each plant species, however, it can be influenced by chemical and physical factors of the soil. In relation to the chemical factors, it is necessary to correct the pH of the soil, performed with the practice of liming, with by the plaster. However, gypsum leaches some nutrients to deeper layers of soil. The management system most adopted is the no tillage, which, due to its implementation and maintenance characteristics, has been causing soil compaction. Therefore, understanding the movement of nutrients in a soil with high density becomes important so that future corrections in the form of soil management are adopted. This experiment aims at the protection generated by compaction, such as isolated and combined applications of Limestone and Plaster, without any compaction process, such as magnesium, potassium and aluminum saturation in clayey Oxisol under SPD. An experimental area was located at the Agronomic Institute of Paraná, in Santa Teresa do Oeste. The treatments consisted of compaction levels, combined with an application of gauge and agricultural gypsum. The experiment was organized in ICD in a striped scheme. In order to evaluate soil production, samples were taken before planting and after soybean harvest and, to determine the rates of movement, soil chemical analyzes of samples prior to the implantation of the experiment were done at 3, 6, 9 and 12 months after soybean sowing. A statistic was made using software R and Sisvar 5.6 and, through the software Statistic, was applied to a mathematical program of prediction of the movement of nutrients in the soil. Based on the analogues, a worse structural condition was identified in the treatments that received the highest soil compaction. The nutrient movement (Ca, Mg and K) and soil saturation were not extensive to the soil and over time were influenced by the soil structural state and the combined applications of gypsum and limestone. This work was carried out with the support of the Coordination of Improvement of Higher Level Personnel (CAPES) - Financing Code 001.